Inhibition of Wnt signaling induces amyloidogenic processing of amyloid precursor protein and the production and aggregation of Amyloid-β (Aβ)42 peptides - Tapia-Rojas, Cheril; Burgos, Patricia V.; Inestrosa, Nibaldo C. (My University, 2016)
Alzheimer's disease (AD) is the most common neurodegenerative disorder and the most frequent cause of dementia in the aged population. According to the amyloid hypothesis, the amyloid-beta (A beta) peptide plays a key role in the pathogenesis of AD. A beta is generated from the amyloidogenic processing of amyloid precursor protein and can aggregate to form oligomers, which have been described as a major synaptotoxic agent in neurons. Dysfunction of Wnt signaling has been linked to increased A beta formation; however, several other studies have argued against this possibility. Herein, we use multiple experimental approaches to confirm that the inhibition of Wnt signaling promoted the amyloidogenic proteolytic processing of amyloid precursor protein. We also demonstrate that inhibiting Wnt signaling increases the production of the A beta(42) peptide, the A beta(42)/A beta(40) ratio, and the levels of A beta oligomers such as trimers and tetramers. Moreover, we show that activating Wnt signaling reduces the levels of A beta(42) and its aggregates, increases A beta(40) levels, and reduces the A beta(42)/A beta(40) ratio. Finally, we show that the protective effects observed in response to activation of the Wnt pathway rely on beta-catenin-dependent transcription, which is demonstrated experimentally via the expression of various 'mutant forms of beta-catenin'. Together, our findings indicate that loss of the Wnt signaling pathway may contribute to the pathogenesis of AD.
Keywords: amyloid-beta; app; gsk-3 beta; wnt signaling; wnt target genes; wnt/beta-catenin